Návrh marketingového mixu společnosti - Rambousková, Ivona (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Bakalářská práce je zaměřena na marketingový mix konkrétní společnosti. Teoretická kapitola obsahuje seznámení s marketingovým prostředím a jednotlivými nástroji marketingového mixu. V analytické kapitole je provedena analýza aktuálního stavu konkrétní společnosti a analýza marketingového prostředí. Návrhová kapitola obsahuje doporučení vedoucí ke zlepšení situace vybrané společnosti.

The bachelor’s thesis is focused on a marketing mix of a particular company. The theoretical chapter contains a familiarization with a marketing environment and component instruments of a marketing mix. In the analytical chapter, there is performed an analysis of the particular company’s present situation and an analysis of the marketing environment. The proposal chapter contains recommendations leading to an improvement of the chosen company’s situation.
Proposal of a Marketing Mix for Company
Keywords: marketing; marketingový mix; 4P; společnost; produkt; zákazník; marketing; marketing mix; 4P; company; product; customer